Numerical Investigation of Critical Velocity in Reduced Scale Tunnel Fire with Constant Heat Release Rate - Ruben Mouangue; Philippe M. Onguene; Justin T. Zaida; Henri P. F. Ekobena (Journal of Combustion)
When a fire occurs in a tunnel in the absence of sufficient air supply, large quantities of smoke are generated, filling the vehicles and any space available around them. Hot gases and smoke produced by fire form layers flowing towards extremities of the tunnel which may interfere with person’s evacuation and firefighter’s intervention. This paper carries out a numerical simulation of an unexpected fire occurring in a one-way tunnel in order to investigate for the critical velocity of the ventilation airflow; this one is defined as the minimum velocity able to maintain the combustion products in the downstream side of tunnel. The computation is performed successively with two types of fuels representing a large and a small heat release rate, owing to an open source CFD code called ISIS, which is specific to fires in confined and nonconfined environments. It is indicated that, after several computations of full-scale fires of 43.103 and 19.103 kJ/kg as heat release rate, the velocities satisfying the criterion of healthy environment in the upstream side of the tunnel are 1.34 m/s and 1.12 m/s, respectively.